Coronary artery aneurysms of unknown origin in a 14-year-old girl. Issue 2 (February 2022) - Toyoshima, Yuka; Tsuda, Etsuko; Kato, Yoshiaki; Iwasa, Tohru; Sakaguchi, Heima; Shimahara, Yusuke; Tabata, Shinya; Ikedo, Taichi; Shiraishi, Isao; Kurosaki, Kenichi
Abstract: The case of a 14-year-old girl with acute myocardial infarction due to coronary artery aneurysms (CAAs) of unknown origin, which resembled coronary artery lesions caused by Kawasaki disease, is reported. She was transferred to our hospital due to chest pain with ST-T elevation. She had no history of Kawasaki disease. On the first admission, she was misdiagnosed with acute myocarditis. Then, 54 days later, she experienced chest pain with exertional dyspnea. Her electrocardiogram showed negative T waves in the chest leads. A CAA of the left coronary artery was suspected on two-dimensional echocardiography. Coronary angiograms showed 90% stenosis and multiple CAAs of the left anterior descending artery and the bifurcation of the left coronary artery. Both the right coronary artery and left circumflex artery were occluded. A left ventriculogram showed dyskinesis and an aneurysm at the apex. She underwent triple-vessel coronary artery bypass grafting, and her symptoms improved. In addition, an intracranial aneurysm was also found on cerebral angiography. There were no specific laboratory findings other than SS-A antibodies. It was suspected that the weakness of the vessels was related to the disease. It may have been a different disease that was never previously detected, but her CAAs were Kawasaki-like CAAs. <Learning objective: A timely precise diagnosis of acute myocardial infarction is unlikely to be made in children because they are rare. The present patient was initially misdiagnosed as having acute myocarditis, because the coronary arteries could not be detected by two-dimensional echocardiography. Either computed tomographic angiography or magnetic resonance angiography is recommended in patients with ST-T abnormalities on the electrocardiogram if it is difficult to identify the coronary arteries. In this case, the patient had a rare coronary artery disease in which the cause of the coronary artery aneurysms was unknown.